Integrating LLM-based agents with uncertainty-aware optimization for water-energy-carbon nexus management in irrigation districts - Lei Yu; Zhikai Li; Kai Huang; Fulin Li; Zixiang Lu; Yurui Fan; Yanan Jiang; Chenglong Zhang; Guangtao Fu (Water Research, 2027)

Thaw-window mismatch in soil organic-pollutant fate under freeze–thaw cycles: redistribution, boundary-export risk, and adaptive control - Zijing Wu; Minjie Zhao; Dong Yu; Jinyang Yu; Hanshuang Liu; Zhiliang Zhao; Chenglong Yu; Shengyan Pu (Water Research, 2026)

Dissolved organic matter molecular composition links water chemistry, microbial functional potential, and nitrous oxide variability in a temperate estuary - Chenglong Han; Qianqian Li; Xinyi Li; Zixu Wang; Xue Yu; Xueqiang Lu (Water Research, 2026)

Arginine and putrescine ameliorate heat stress-induced testicular inflammation and apoptosis via inhibiting endoplasmic reticulum stress in mice - Kun Wu; Chenglong Yu; Guangmang Liu; Yong Zhuo; Bin Feng; Lianqiang Che; Shengyu Xu; Lun Hua; Jian Li; Zhengfeng Fang; De Wu; Yan Lin (Theriogenology, 2026)

Study on the improvement effect of water-based polyurethane/cellulose acetate composite on silty clay for slope ecological restoration in seasonally frozen soil regions - Xinhao Wu; Chenglong Yu; Libo Liu; Huanan Liu; Jiquan Zhang; Yichen Zhang; Qinze Du; Haoxin Chen (Ecological Engineering, 2026)

From electrode activity to reactive zone control: 3D electrochemical remediation of chlorinated hydrocarbon contaminated groundwater - Chengxiang Cui; Dong Yu; Hongqing Zhu; Chenglong Yu; Shengyan Pu (Chemical Engineering Journal, 2026)

Understanding the global interdependencies of SDGs via causal network analysis - Yu Ding; Xi Chen; Chenyang Shuai; Chenglong Wang; Zhenci Xu; Bu Zhao (Sustainable Production and Consumption, 2026)

Unveiling the spatial-temporal virtual water use of China's rural residents through trade network - Xi Chen; Yaqi Yang; Shunqiang Sun; Xinye Yu; Chenglong Wang; Chenyang Shuai; Bu Zhao (Journal of Rural Studies, 2026)

Toward precise management of groundwater by combined heavy metal(loid)s contamination at industrial sites: A machine learning driven source-to-risk zoning framework - Hanshuang Liu; Qingnan Yue; Dong Yu; Chenglong Yu; Geng Yang; Xingtao Wang; Qinglong Song; Zijing Wu; Shengyan Pu (Environmental Pollution, 2026)

Mineral phase transformation drives molecular fractionation of dissolved organic matter during organic acid-driven weathering of bauxite residue - Chenglong Lu; Songlin Wu; Fang You; Dingyi Yu; Jitraporn Vongsvivut; Annaleise Klein; Lars Thomsen; David Parry; Ting-Shan Chan; Longbin Huang (Chemical Geology, 2026)

Humic acid–mediated shift in •OH formation location enhances contaminant degradation during oxygenation of surface-adsorbed Fe(II) - Wenwen Ji; Chenglong Yu; Yuying Tang; Benyin Zhou; Hanshuang Liu; Shengyan Pu (Chemical Geology, 2026)

Preparation of a MOF-derived Mn-Ti catalyst and its simultaneous removal of NOx and toluene: Strong metal-support interaction and Lewis acid sites - Yongchao Zhong; Dan He; Qiangwei Lu; Lu Wang; Yunkuo Luo; Dongliang Zhang; Chaochao Li; Lin Li; Fengying Li; Xiang Tu; Chenglong Yu (Journal of Environmental Chemical Engineering, 2026)

A flavor-modification strategy for Pu-erh raw tea to selectively rebalance key aroma–taste drivers and improve drinking comfort based on supercritical CO2 technology - Dan Wang; Chenglong Wang; Siqian Guo; Wentao Gao; Lei Zhang; Kexi Ma; Yu Lan; Jingming Li (Food Research International, 2026)

Quantification of sediment redox capacities under different Eh conditions by a modified electrochemical method - Yingxiao Tian; Peng Zhang; Yuxi Lu; Yanping Cui; Jinguang Xiao; Chenglong Yu; Songhu Yuan (Chemical Geology, 2026)

Climate Warming Intensifies Cascading Risks Along the Heatwave‐Drought‐Wildfire Hazard Chain in Northeast Asia - Dan Liu; Chenglong Yu; Rui Feng; Yonglan Qian; Qingtao Meng (International Journal of Climatology, 2026)
Northeast Asia is one of the Northern Hemisphere mid‐ to high‐latitude regions most sensitive to global warming, where high temperatures, drought and wildfires have become increasingly frequent and concurrent, yet their cascading linkages remain poorly quantified within a unified daily‐scale framework. We integrate daily observations from 829 meteorological stations, soil moisture from a land‐surface data assimilation product and MODIS active‐fire detections and use a boosting‐based ensemble machine‐learning model to substantially improve the simulation of 0–10 cm relative soil moisture. On this basis, we derive triggering thresholds along a heatwave‐drought‐wildfire (HDW) cascading hazard chain. The 6‐day moving mean of daily maximum temperature (AUC = 0.74) defines the key temporal window for drought triggering, with thresholds in spring and autumn generally lower than those in summer. The mean triggering rate of the HDW hazard chain during 2017–2023 (0.18) is 157% higher ( p −1 ), pointing to a potential risk of irreversible change. By contrast, under progressively strengthened ignition control and fire management systems, the triggering rate in Northeast China shows a decreasing trend (−0.002 year −1 ), suggesting that policy interventions may partially offset the amplifying effect of climate warming on the hazard chain. This study links, at the daily scale, cumulative heat exposure, soil‐drought thresholds and wildfire occurrence along a cascading pathway and provides a quantitative basis for improving compound hazard risk assessment and designing regionally differentiated fire management strategies.

Study on the Coupling Mechanism and Quantitative Model of Compaction Damage in Saturated Concrete Under Cyclic Loading - Yuxue Sun; Deyu Guo; Hao Yu; Yanshun Liu; Xiao Zhang; Zhanchao Yin; Xianghui Li; Chenglong Hao (Rock Mechanics and Rock Engineering, 2026)

Study on the macro-microscopic damage deterioration mechanism of weathered dacite under freeze–thaw cycles - Junqi Yu; Hui Deng; Chenglong Yang (Bulletin of Engineering Geology and the Environment, 2026)

Study on phase occurrence and pyrolysis kinetic mechanism of barium slag: based on mineralogical characterization and TG-IR-MS coupled analysis - Chenglong Jian; Jinbang Zhang; Licha Meng; Qiuhong Zhang; Yu Zhang; Dengpan Nie (Minerals Engineering, 2026)

A plant-free push–pull system using sustained-release electrospun micro-/nanofibers for insect behavioral manipulation - Chenglong Cui; Xiwei Xia; Zhimin Wang; Ertao Li; Huanhuan Dong; Jiaan Shen; Yujun Sun; Yu Peng; Kebin Li; Jiao Yin (Journal of Pest Science, 2026)

GAN-FixMatch: A generative–semi-supervised deep learning framework for small-sample quantitative analysis in near-infrared spectroscopy of agricultural and pharmaceutical materials - Peng Li; Chenglong Qiu; Jinlong Duan; Yao Qin; Mingxing Li; Dandan Zhai; Xile Cheng; Yu Yang (Analytica Chimica Acta, 2026)

Nonlinear drivers of canopy and surface urban heat islands across China’s climate zones: marginal and interaction effects from explainable machine learning - Cong Wen; Ali Mamtimin; Haitao Wang; Yu Wang; Haotong Liu; Hajigul Sayit; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Yisilamu Wulayin; Fan Yang; Chenglong Zhou; et al. (Sustainable Cities and Society, 2026)

Mechanism of pyrene remediation in soil by biochar-immobilized laccase - Babar Hussain; Sami Ullah; Nadeem Iqbal; You Wu; Hui Ma; Chenglong Yu; Shiyong Sun; Shengyan Pu (Environmental Research, 2026)

PFOS exposure at environmentally relevant concentrations promote papillary thyroid carcinoma progression through PI3K/AKT/mTOR-mediated epithelial-mesenchymal transition - Yaling Yu; Yi Wang; Xuling Su; Zhenzhen Cai; Qianqian Wang; Chenglong Wang; Yiwei Zhao; Tonghui Zhang; Danjie Hu; Zhiyan Liu (Environmental Research, 2026)

Observed and modeled interactions between atmospheric pollutants and urban thermal environment in an arid city: Urumqi as a case study - Cong Wen; Yu Wang; Ali Mamtimin; Jian Peng; Hajigul Sayit; Jiali Feng; Meiqi Song; Jiacheng Gao; Ailiyaer Aihaiti; Junjian Liu; Yisilamu Wulayin; Chenglong Zhou; et al. (Atmospheric Environment, 2026)

Sex-specific associations of low-level urinary albumin-creatinine ratio with mortality and adverse cardiac events in older adults - Cammie Tran; Rowan G. Walker; Hans G. Schneider; Que T. Lam; Chenglong Yu; Zhen Zhou; Flavia Cicuttini; Sultana Monira Hussain; Paul Lacaze; John J. McNeil (GeroScience, 2026)
Albuminuria is traditionally defined using fixed urinary albumin–creatinine ratio (UACR) thresholds, although cardiovascular disease (CVD) risk has been reported to increase continuously across the UACR spectrum. Whether these associations are present in healthy older adults and differ by sex remains unclear. We examined sex-specific associations between low-level UACR, mortality, and cardiovascular outcomes in older adults with preserved kidney function. From the ASPirin in Reducing Events in the Elderly (ASPREE) study, we included 5396 males and 6305 females aged ≥ 70 years with baseline UACR and eGFR ≥ 60 mL/min/1.73 m 2 ). Sex-stratified Cox models examined associations between UACR quintiles (Q) and mortality, CVD, major adverse cardiovascular events (MACE), and stroke, using Q1 as reference. Over a median follow-up of 8.3–8.6 years, increasing UACR was associated with progressively higher risk of all-cause mortality in both sexes, despite most values being below the guideline thresholds. Mortality risk reached statistical significance for males from Q4 (HR 1.45; 95% CI 1.18–1.77) and females from Q2 (HR 1.33; 95% CI 1.04–1.71). Males also had a statistically significant increase in CVD from Q4 (HR 1.32; 95% CI 1.03–1.70) and MACE and stroke in Q5 (HR 1.61; 95% CI 1.25–2.07 and HR 1.96; 95%CI 1.38–1.78). Despite an increasing trend in females, adverse cardiovascular outcomes did not reach significance. UACR levels below guideline thresholds were associated with all-cause mortality in both sexes, with increased cardiovascular disease predominately observed in men. These findings support a continuous relationship between UACR and risk and suggest that even low-level albuminuria may have prognostic significance in healthy older adults.

Phosphorus speciation and leaching behavior in nitric acid leaching residue of rare earth phosphate ore - Licha Meng; Qian Shang; Jinbang Zhang; Chenglong Jian; Jin Fang; Dengpan Nie; Yu Zhang (Journal of Environmental Management, 2026)

Waste PET-derived Co-MOF catalytic membrane: Achieving high-efficiency and sustainable antibiotics removal from water through visible-light-activated peroxymonosulfate - Huamei He; Meixuan Xin; Jun Wang; Xi Chen; Feifei Wei; Qiangbin Yang; Chenglong Yu; Guangyong Zeng; Chong-Chen Wang (Desalination, 2026)

Biodegradable mulch films divergently regulate soil carbon cycle by reshaping microbial communities and functional genes - Haiyun Zhang; Shutong Yu; Weiguang Lv; Xilong Wang; Ping Lu; Hanlin Zhang; Juanqin Zhang; Naling Bai; Chenglong Xu; Xianpu Zhu; Shuangxi Li (Journal of Hazardous Materials, 2026)

Release behavior and risk assessment of heavy metals from nitric acid leach residue of phosphate ore - Licha Meng; Qian Shang; Chenglong Jian; Jinbang Zhang; Feng Li; Jin Fang; Dengpan Nie; Yu Zhang (Journal of Hazardous Materials, 2026)

The bio-corrosion mechanisms, mathematical modelling and machine learning applications in concrete structures: a systematic review - Chenglong Yu; Xiaojie Chen; Zhihao Feng; Hui Rong; Xiaofeng Zhou (Biofouling, 2026)

Arid and cool climate transition during the evolution of the Jehol Biota and its implications - Zhaoxia Ge; Jiaheng Shen; Huan Yang; Xiaoqing Liu; Zhiqiang Yu; Chenglong Deng; Haibin Wu; Zhonghe Zhou (Global and Planetary Change, 2026)

Coupled hydrochemical–microbial approach to groundwater pollution in covered and exposed karst systems - Geng Yang; Qinglong Song; Xingtao Wang; Qingnan Yue; Yi Chen; Hui Ma; You Wu; Chenglong Yu; Shengyan Pu (Environmental Pollution, 2026)

Quantifying the impact of nanoplastics and natural particles on copper accumulation and distribution in zebrafish: Coupling in vivo tests with toxicokinetic modeling - Xiaorong Luo; Xue Yu; Chenglong Han; Ning Gao; Xunqiang Mo; Jianfeng Feng; Xueqiang Lu (Environmental Pollution, 2026)

Catalytic role of LiCl in the partial decomposition of phosphate tailings: experimental and theoretical calculations - Jinbang Zhang; Chenglong Jian; Licha Meng; Xiong Hong; Qiao Lu; Yu Zhang (Chemical Engineering Journal, 2026)

Enhancement of the crack and erosion resistance of silty clay under freeze–thaw cycles: Synergistic effect of sisal fiber–fly ash - Jiashun Ding; Huanan Liu; Dan Qiu; Lianghao Zhai; Bo Qi; Chenglong Yu; Keyu Yue (Journal of Mountain Science, 2026)

Functional group-directed electron shuttling by adsorbed humic acid exciting nontarget reactions and their enhancement non-radical oxidation in H2O2-based aquifer remediation - Peng Wang; Pei An; Chenlong Wang; Zhaoyu Chen; Chenglong Yu; Wen Zhang; Shengyan Pu (Water Research, 2026)

β-cyclodextrin and ZnCo-layered double hydroxides composite modified electrode for ultrasensitive detection of carbendazim in water - Changchun Zhu; Qiang Xue; Chenglong Yu; Hongqing Zhu; Yuanying Huang; Yao Liu; Zeyu Liu; Haijiao Xie; Shengyan Pu (Journal of Hazardous Materials, 2026)

Cerium-driven electronic modulation in CoMn2O4 spinel: Uniting lattice and gaseous oxygen pathways for accelerated toluene destruction - Weicheng Xu; Yun Liao; Hong Wu; Xueding Jiang; Linghe Song; Zhang Liu; Chenglong Yu; King Lun Yeung; Daiqi Ye (Journal of Hazardous Materials, 2026)

Text-Guided Coarse-to-Fine Fusion Network for robust remote sensing visual question answering - Zhicheng Zhao; Changfu Zhou; Yu Zhang; Chenglong Li; Xiaoliang Ma; Jin Tang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Quantifying freeze-thaw erosion dynamics in retrogressive thaw slumps: integrating geophysical and experimental approaches - Chenglong Jiao; Fujun Niu; Jing Luo; Peifeng He; Fan Yu (CATENA, 2025)

Assessing the impact of upstream water quality levels on downstream economic growth in China: A high-resolution panel study - Yu Ding; Chenglong Wang; Chenyang Shuai; Xi Chen; Jingran Sun; Bu Zhao (Journal of Geographical Sciences, 2025)

Improving coking wastewater treatment efficiency in the tidal flow constructed wetland via biochar-immobilized microbes - Xuejiao An; Chenglong Yu; Hanguang Li; Guanghua Huo; Hui Lu; Huoyong Jiang; Xiaomei Zheng; Liuhua Guo; Qinghua Zhang (Process Safety and Environmental Protection, 2025)

Identifying urban river pollution sources from wet-weather discharges using an integrated deep learning and data assimilation approach - Hongzhe Pan; Yiping Li; Jiangjiang Zhang; Chenglong Cao; Yu Cheng; Yuxuan Zhou; Yaning Wang; Song Bai; Jun Liu; Qiaoyi Jin; Carlo Gualtieri (Journal of Hydrology, 2025)

Rapid self-heating synthesis of nitrogen-doped carbon materials for peroxymonosulfate activation to degrade benzohydroxamic acid: Crucial role of persistent free radicals - Qianzhen Fang; Xiaofei Tan; Jian Ye; Hui Sun; Shujing Ye; Hailan Yang; Chenglong Yu; Hongqin Zhu; Qingkai Shi; Fanzhi Qin; Shengyan Pu (Bioresource Technology, 2025)

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

High-resolution magnetostratigraphy of the Lower Cretaceous Dabeigou Formation in the Luanping Basin, northern China - Zhongshan Shen; Zhiqiang Yu; Zuohuan Qin; Dangpeng Xi; Gang Li; Huaiyu He; Chenglong Deng; Zhonghe Zhou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

CTAB-Assisted, controlled preparation of a CeZrOx/CuSAPO-34 catalyst and its performance for the synergistic removal of NOx and toluene from flue gas - Qian Zhou; Xuehui Jia; Rong Liu; Fangfei Liu; Han Zhang; Dan Hou; Lu Wang; Yunkuo Luo; Bichun Huang; Hong Huang; Xia Gong; Chenglong Yu (Journal of Environmental Chemical Engineering, 2025)

Study on the antioxidant defense of Pacific oysters (Crassostrea gigas) against sulfonamide antibiotics - Hao Chen; Liping You; Jing Sun; Hao Yu; Wei Sun; Changlin Song; Bo Su; Chenglong Ji; Lin Ye; Shujun Li; Yanmin Qi; Yuanqing Ma (Aquaculture, 2025)

Accurate and simple determination of sediment redox capacity by a modified chemical probe method: Implications to contaminant remediation - Yuxi Lu; Rong Chen; Weijun Zhao; Peng Zhang; Shukui Zhu; Chenglong Yu; Songhu Yuan (Water Research, 2025)

An ensemble learning-based approach for large-scale cultivated land quality monitoring - Dan Liu; Chenglong Yu; Rui Feng; Shiping Yin (Ecological Modelling, 2025)

The regulatory role of dissolved oxygen in N-doped biochar-driven nonradical oxidation - Hongqing Zhu; Hui Ma; Lanxin Xu; Dong Yu; Shuang Zhong; Ying Chen; Tianrong Guo; Meththika Vithanage; Chenglong Yu; Shengyan Pu (Chemical Engineering Journal, 2025)

Soil pH and precipitation controls on organic carbon retention from organic amendments across soil orders: A meta-analysis - Bin Wu; Tongshuo Bai; Wenjuan Yu; Tongbin Zhu; Daming Li; Chenglong Ye; Manqiang Liu; Shuijin Hu (Soil Biology and Biochemistry, 2025)

Sluice gate flow model considering section contraction, velocity uniformity, and energy loss - Yanshun Liu; Chenglong Hao; Xiao Zhang; Hao Yu; Yuxue Sun; Zhanchao Yin; Xianghui Li (Journal of Hydrology, 2025)

Unveiling the overlooked silent threat: High-throughput suspect screening of antibiotics and multidimensional heterogeneity in aquatic ecosystems of megacity - Tianrong Guo; Qingnan Yue; Yu Hou; Yi Chen; Dong Yu; Geng Yang; Chenglong Yu; Yuping Zeng; Yanqi Feng; Shengyan Pu (Journal of Hazardous Materials, 2025)

Chitosan/oxidized cellulose composite nanofiber sponges: a rapid and effective hemostasis strategy for non-compressible hemorrhage - Zhan Zhang; Zhiyuan Lin; Chenglong Yu; San Ieng Lei; Lu Wang; Fujun Wang; Jing Gao; Wenbo Meng (Carbohydrate Polymers, 2025)

Regulating the Cu-Ce interaction of CuCeOx/SAPO-34 catalysts to achieve a wide reaction temperature window for the collaborative synergistic removal of NOx and toluene at low temperatures and reaction mechanisms - Rong Liu; Xuehui Jia; Lin Li; Fengying Li; Xiang Tu; Weicheng Xu; Hansun Fang; Danping Li; Hong Huang; Chenglong Yu (Journal of Hazardous Materials, 2025)

Experimental and mechanistic study on liquid–liquid equilibrium for the separation of cyclohexane and ethyl acetate using imidazolium ionic liquids - Xia Li; Shuyan Liu; Yahui Yin; Weilian Zhang; Chenglong Sun; Zilong Yu; Yu Zhou; Chun Zhao; Zhiguo Liu; Hongfei Xiang; Xianzhen Xu (Fuel, 2025)

Direct photodegradation of aromatic carbamate pesticides: Kinetics and mechanisms in aqueous vs. non-aqueous media - Yufan Yuan; Danping Li; Huajun Huang; Jinbao He; Chenglong Yu; Yanpeng Gao; Davide Vione; Hansun Fang (Journal of Hazardous Materials, 2025)

Mechanistic insights into the chlorination volatilization of oxidized heavy metals via novel staggered chlorination roasting - Chenglong Lu; Xuan Yu; Guohao Yang; Qianqian Guo; Long Jiao; Jinxiang Lin; Kai Deng; Yanjun Hu (Waste Disposal & Sustainable Energy, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Freezing-Induced Redistribution of Fe(II) Species within Clay Minerals for Nonlinear Variations in Hydroxyl Radical Yield and Contaminant Degradation - Dong Yu; Hongbin Peng; Chenglong Yu; Wenwen Ji; Xin Wang; Shengyan Pu (Journal of Earth Science, 2025)

RealFusion: A reliable deep learning-based spatiotemporal fusion framework for generating seamless fine-resolution imagery - Dizhou Guo; Zhenhong Li; Xu Gao; Meiling Gao; Chen Yu; Chenglong Zhang; Wenzhong Shi (Remote Sensing of Environment, 2025)

Molecular biomarkers for the prognosis of breast cancer: role of amino acid metabolism genes - Yudong Zhou; Shibo Yu; Lizhe Zhu; Yalong Wang; Chenglong Duan; Danni Li; Jinsui Du; Jiaqi Zhang; Jianing Zhang; Ruichao Ma; Jianjun He; Yu Ren; et al. (Journal of Physiology and Biochemistry, 2025)
The development of precise molecular biomarkers for breast cancer prognosis holds immense potential to improve treatment outcomes. This study aimed to investigate the role of amino acid metabolism genes as predictive markers for breast cancer prognosis and their association with the immune-tumour microenvironment. By employing advanced machine learning algorithms and bioinformatics analysis techniques, the impact of amino acid metabolism-related genes (AAMRGs) on the immune status and overall survival of patients with breast cancer was examined. An AAMRG-based risk model was established to assess the prognostic significance. Validated risk models (AIMP2, IYD, and QARS1) accurately predicted patient outcomes [1 y: 0.87 (0.96–0.78); 3 y: 0.82 (0.87–0.76); 5 y: 0.80 (0.86–0.75)]. Furthermore, this study revealed evidence suggesting that QARS1 may influence breast cancer cell proliferation through methionine metabolism. This analysis provides valuable insights into the mechanisms of breast cancer, emphasizing the significance of AAMRGs as prognostic biomarkers and potential therapeutic targets for optimizing personalized treatment strategies.

Deciphering the microbiome, lipopolysaccharides, and metabolome interplay: Unveiling putrescine's mechanism for enhancing sperm quality in heat-stressed boars - Chenglong Yu; Hao Li; Lun Hua; Lianqiang Che; Bin Feng; Zhengfeng Fang; Shengyu Xu; Yong Zhuo; Jian Li; De Wu; Junjie Zhang; Yan Lin (Theriogenology, 2025)

Mechanism of mineral adsorption enhancing the reduction of hexavalent chromium by natural organic matter - Peng Zhang; Yiran Liu; Yingxiao Tian; Chenglong Yu; Songhu Yuan (Geochimica et Cosmochimica Acta, 2025)

Study on vapor–liquid equilibrium for the separation of ethyl acetate and isopropanol azeotrope using phosphonium-based ionic liquids - Yahui Yin; Shuyan Liu; Xia Li; Zilong Yu; Weilian Zhang; Chenglong Sun; Chun Zhao; Xianzhen Xu (Fuel, 2025)

Phase reconstruction behavior and mechanism analysis of the electrolytic manganese residue decoupled residue pyrolysis process - Qian Shang; Chenglong Jian; Qianlin Chen; Yunqiu Liu; Yu Zhang; Dengpan Nie (Journal of Environmental Management, 2025)

Assessment of CO2 fluxes in the hinterland of the Gurbantunggut Desert and its response to climate change - Ali Mamtimin; Gulnur Amar; Yu Wang; Jian Peng; Hajigul Sayit; Jiacheng Gao; Kun Zhang; Meiqi Song; Ailiyaer Aihaiti; Cong Wen; Fan Yang; Wen Huo; et al. (Journal of Environmental Management, 2025)

Exaptation of pectoral fins for olfaction in the spiny red gurnard (Chelidonichthys spinosus) through an ancient receptor - Lisen Li; Deqian Fan; Chenglong Zhu; Zhuoya Liu; Wenji Huang; Peidong Xin; Huishan Yue; Mengying Li; Yufei Wang; Wenjie Xu; Jiangmin Zheng; Ye Li; et al. (Science China Life Sciences, 2025)

Adsorption of oxidized humic acid onto redox-inert mineral surfaces induces formation of hydroxyl radicals and carbon dynamics - Shengyan Pu; Xinyi Li; Zhongquan Liu; Peng Zhang; Chenglong Yu (Water Research, 2025)

Synergistic functionality of metal–organic framework-cellulose composites structures for advanced high-performance energy materials - Chenglong Fu; Xianxin Han; Yu Zhang; Jinwen Hu; Jian Du; Haisong Wang (Chemical Engineering Journal, 2025)

Synergistic interaction of char-volatile/volatile-volatile on PAHs formation during waste printed circuit boards pyrolysis: Evolution pathway and mechanisms - Yingwen Zhang; Chunbao Zhou; Yang Liu; Bang Yao; Li Chao; Dekai Fan; Mengyan Yu; Chenglong Liu; Jianjun Dai (Chemical Engineering Journal, 2025)

Exploring the antibiofilm potential of chitosan nanoparticles by functional modification with chloroquine and deoxyribonuclease - Wenyang Xia; Jun Li; Qiuchen Cai; Changxu Deng; Zubin Zhou; Xiaowei Yu; Chenglong Huang; Biao Cheng (Carbohydrate Polymers, 2025)

Grazing weakens the carbon sequestration capacity of dry temperate grassland ecosystems in Central Asia - Yuangang Wang; Geping Luo; Chaofan Li; Yu Zhang; Chenglong Zhang; Xiaotong Yu; Binbin Fan; Wenqiang Zhang; Mingjuan Xie; Yujia Liu (CATENA, 2025)

Increased Mineral‐Associated Organic Carbon and Persistent Molecules in Allochthonous Blue Carbon Ecosystems - Yuan Li; Chuancheng Fu; Chenglong Ye; Zhaoliang Song; Yakov Kuzyakov; Tony Vancov; Laodong Guo; Zhongkui Luo; Lukas Van Zwieten; Yidong Wang; Yu Luo; Weiqi Wang; et al. (Global Change Biology, 2025)
Coastal wetlands contain very large carbon (C) stocks—termed as blue C—and their management has emerged as a promising nature‐based solution for climate adaptation and mitigation. The interactions among sources, pools, and molecular compositions of soil organic C (SOC) within blue C ecosystems (BCEs) remain elusive. Here, we explore these interactions along an 18,000 km long coastal line of salt marshes, mangroves, and seagrasses in China. We found that mineral‐associated organic C (MAOC) is enriched in BCEs dominated by allochthonous inputs and abundant active minerals, leading to an increased proportion of persistent organic molecules. Specifically, soils with large allochthonous inputs (> 50%) are characterized by a substantial contribution of MAOC (> 70%) to total SOC with a notable preservation of lipids (36%) across salt marshes, mangroves, and seagrasses. The burial of allochthonous particles, derived from external sources such as rivers or tidal influxes, facilitates the formation of stable MAOC through binding to mineral surfaces or occlusion within microaggregates. The proportions of particulate organic C (POC) and MAOC are important predictors for molecular compositions of soil organic matter. Lipid proportions within molecular composition decrease as POC and autochthonous C proportions increase. These findings provide new insights into the coupled control over SOC sequestration in BCEs, emphasizing the role of allochthonous inputs, proportions of carbon pools, and persistent organic components.

Unveiling electron transfer and radical transformation pathways in coupled electrocatalysis and persulfate oxidation reactions for complex pollutant removal - Shuai Li; Xueding Jiang; Weicheng Xu; Meng Li; Zhang Liu; Wei Han; Chenglong Yu; Jiesen Li; Hailong Wang; King Lun Yeung (Water Research, 2024)

Spatial and temporal characteristics of volatiles in the Cenozoic mantle beneath eastern China - Qianling Zhou; Chenglong Yu; Yang-Yang Wang; Dongbo Tan; Erhao Shan; Dongyong Li; Xiaoxia Wang; Yigan Lu; Fengtai Tong; Yilin Xiao (Lithos, 2024)

Spatial distribution and migration characteristics of heavy metals at an abandoned industrial site in the Southwest of China - Jiayi Deng; Jingyang Yu; Xingtao Wang; Dong Yu; Hui Ma; You Wu; Chenglong Yu; Shengyan Pu (Journal of Hazardous Materials, 2024)

Biochar-bacteria coupling system enhanced the bioremediation of phenol wastewater-based on life cycle assessment and environmental safety analysis - Xuejiao An; Yanlin Wang; Chenglong Yu; Xiaojing Hu (Journal of Hazardous Materials, 2024)

Beach erosion and typhoons reduce green turtle nesting grounds on the Xisha Islands, South China Sea - Ting Zhang; Chenglong Zhang; Yupei Li; Yangfei Yu; Xiaoyu An; Yongkang Jiang; Jichao Wang; Liu Lin; Hai-Tao Shi (Frontiers in Marine Science, 2024)
Introduction Sea turtles are ideal flagship and umbrella species for marine biodiversity conservation. The quality of nesting grounds is crucial for the successful reproduction of sea turtles, as it determines whether they can successfully nest and hatch. The Xisha Islands represent the largest remaining nesting grounds for green turtles in China. However, they face numerous threats and lack management guidelines for nesting ground restoration. Methods In this study, we continuously monitored the beach changes and coastal erosion on North Island, which is located in the northern region of the Xisha Islands, from 2019 to 2022. Results From 2020 to 2022, the beach area on North Island decreased annually by 11,800 m 2 , accounting for 24.39% of the beach area in 2020. The proportion of suitable nesting sand types (including coarse and medium sands) also decreased annually, with a reduction of 40–70% on the southern beach of North Island. The peak nesting period of green turtles on North Island coincides with the frequent occurrence of typhoons in the South China Sea, causing tidal surges that inundate green turtle nests, resulting in an average nest loss rate of 35.25%. Discussion Based on the above threats, it is recommended to promptly initiate habitat restoration in severely eroded areas of green turtle nesting grounds to prevent further declines in nesting area and quality. Additionally, measures such as nest relocation should be implemented to enhance green turtle reproductive success.

Evaluation of groundwater quality with multi-source pollution based on source identification and health risks - Dong Yu; Jiayi Deng; Qing Jiang; Hanshuang Liu; Chenglong Yu; Hui Ma; Shengyan Pu (Science of The Total Environment, 2024)

Dynamic monitoring and counting for lotus flowers and seedpods with UAV based on improved YOLOv7-tiny - Ziwei Lyu; Yu Wang; Chenglong Huang; Guozhong Zhang; Kaiquan Ding; Nanrui Tang; Zhuangzhuang Zhao (Computers and Electronics in Agriculture, 2024)

Quality evaluation and health risk assessment of karst groundwater in Southwest China - Jiayi Deng; Geng Yang; Xinyao Yan; Junyan Du; Qiang Tang; Chenglong Yu; Shengyan Pu (Science of The Total Environment, 2024)

A comprehensive review of the bio-corrosion mechanisms, hydrodynamics and antifouling measures on marine concrete - Xiaojie Chen; Chenglong Yu; Lu Wang; Bo Yu (Ocean Engineering, 2024)

An unknow fault diagnosis Scheme: A novel random deep forest for fault diagnosis of HVACs - Ying Yan; Jianqiang Sun; Chenglong Yu; Xiaorong Sun; Edmond Qi Wu; Tao Li; Jun Cai; Adrian David Cheok (Energy and Buildings, 2024)

Hydrogel microspheres for stem cell recruitment and induction of directed differentiation in osteoarthritis therapy - Han Yu; Huanhuan Luo; Jianping Chen; Xiaodong Hu; Yujiong Chen; Jiaqi Zhong; Botao Liu; Yanfang Liu; Gang Chen; Chenglong Huang; Zhaoxiang Peng (Chemical Engineering Journal, 2024)

Asymmetrical changes of electron-donating and electron-accepting capacities of natural organic matter during its interaction with Fe oxyhydroxides - Yiran Liu; Weijun Zhao; Peng Zhang; Qing-long Fu; Chenglong Yu; Songhu Yuan (Chemical Geology, 2024)

The 2023 Mw7.7 Pazarcik earthquake caused a reversal in vertical motion along the SW branch of the East Anatolian fault - Zheng Gong; Haibing Li; Huiping Zhang; Kerem Kuterdem; Shiguang Wang; Jialiang Si; Yong Zheng; Peng Liang; Chenglong Li; Chuanyou Li; Zhikun Ren; Jingxing Yu; et al. (Journal of Structural Geology, 2024)

The demethylase ALKBH5 mediates ZKSCAN3 expression through the m6A modification to activate VEGFA transcription and thus participates in MNNG-induced gastric cancer progression - Qing Wang; Yefei Huang; Min Jiang; Yu Tang; Qinzhi Wang; Longlong Bai; Chenglong Yu; Xinyue Yang; Kun Ding; Weimin Wang; Jin Bai; Yansu Chen (Journal of Hazardous Materials, 2024)

Experimental investigation of photoelectrical performance and thermal characteristics of ventilated building-integrated photovoltaic system utilizing lightweight and flexible crystalline silicon module - Xinzhu Chen; Chenglong Luo; Jie Ji; Lingping Liu; Xiaoxiao Su; Yanshun Yu; Hua Zhang; Ruili Peng (Journal of Cleaner Production, 2024)

Victoria amazonica-inspired sandwich-structure interfacial solar steam generator - Junjie Pan; Xin Zhang; Chenglong Zhang; Wenfeng Hu; Siyi Bi; Huiqi Shao; Nanliang Chen; Rui Yu; Jinhua Jiang; Guangwei Shao (Chemical Engineering Journal, 2024)

Accumulation rate and sources of plastic marine litter at nesting grounds of green turtles on the North Island of Qilianyu, Xisha Islands, South China Sea - Ting Zhang; Yongkang Jiang; Deqin Li; Chenglong Zhang; Yunteng Liu; Yupei Li; Yangfei Yu; Jichao Wang; Hai-Tao Shi; Liu Lin (Marine Pollution Bulletin, 2024)

Water-exit impact of deep-sea mining vehicles: Experimental and numerical investigations - Xin Huang; Yu Dai; Chenglong Liu; Qiao Su; Xiang Zhu (Ocean Engineering, 2024)

N-octyltrimethylammonium bromide-assisted self-assembly of CoMo precursors to prepare CoMoS/Al2O3 catalysts for highly selective hydrodesulfurization of thiophene - Shuisen He; Xueman Wang; Chenglong Wen; Yu Fan (Fuel, 2024)

Thinning intensity inhibits microbial metabolic limitation and promotes microbial carbon use efficiency in natural secondary forests in the Qinling Mountains - Yahui Song; Hang Yang; Dongcai Huang; Chenglong Yan; Haibin Kang; Haiyu Qi; Hang Yu; Dexiang Wang (Forest Ecology and Management, 2024)

Cellulose nanocrystals intercalated clay biocomposite for rapid Cr(VI) removal - Zilong Deng; Zixuan Wu; Qin Wu; Junlei Yu; Chenglong Zou; Huali Deng; Pingliang Jin; Donglu Fang (Environmental Science and Pollution Research, 2024)

Navigating the green spectrum: an inquiry into low-carbon HRM practices and the influence of perceived supervisor support on employee sustainability in China - Yuguo Jiang; Enock Mintah Ampaw; Hongxiang Yu; Chenglong Wang (Environment, Development and Sustainability, 2024)

D-beta-hydroxybutyrate up-regulates Claudin-1 and alleviates the intestinal hyperpermeability in lipopolysaccharide-treated mice - Ting Wang; Yuchen Zhuang; Chenglong Yu; Zhaobo Wang; Yuan Liu; Qian Xu; Kun Liu; Yanning Li (Tissue and Cell, 2024)

Glu and GSH double-unlocked immunomodulatory tri-cascade nanoreactor for biofilm-infected diabetic wounds healing - Xiaoyu Zhao; Chenglong Xue; Yu Liu; Tao Wang; Qi Shuai (Chemical Engineering Journal, 2024)

Particle size, carbon composition and sources of indoor dust in Nanchang, China - Changwei Zou; Xinpeng Liao; Hong Huang; Yuan Tang; Zhijie Li; Jianlong Li; Chenglong Yu; Fangxu Zhu (Atmospheric Pollution Research, 2024)

Microplastics: A potential proxy for tracing extreme flood events in estuarine environments - Hongyu Chen; Yu Cheng; Ying Wang; Yongcheng Ding; Chenglong Wang; Xuguang Feng; Qinya Fan; Feng Yuan; Guanghe Fu; Bingfei Gao; Kai Liu; Xinqing Zou (Science of The Total Environment, 2024)

Prevalence and distribution of antibiotic-resistant bacteria in the rhizosphere and rhizoplane of Suaeda salsa and Sporobolus alterniflorus grown in a pristine environment - Yu Wang; Fang Yang; Qianwen Liu; Lin Sun; Weihua Chen; Qingfeng Yu; Chenglong Pan; Guanhong Jiang; Xin'an Jiao; Yunzeng Zhang (Applied Soil Ecology, 2024)

A facile, green strategy to synthesize N/P self-doped, biomass-derived, hierarchical porous carbon from water hyacinth for efficient VOCs adsorption - Chenglong Yu; Junhui Dan; Zewei Liu; Jinliang Wang; Jiayang Wang; Hansun Fang; Fayin Lai; Danping Li; Lin Li; Fengying Li; Chunhuo Zhou; Bichun Huang (Fuel, 2024)

Electron transfer processes associated with structural Fe in clay minerals - Chenglong Yu; Ao Qian; Yuxi Lu; Wenjuan Liao; Peng Zhang; Man Tong; Hailiang Dong; Qiang Zeng; Songhu Yuan (Critical Reviews in Environmental Science and Technology, 2024)

Focal mechanism of a Late Triassic large magnitude earthquake along the Longmen Shan fault belt, eastern Tibetan Plateau - Lei Zhang; Haibing Li; Eric C. Ferré; Zhiming Sun; Yu-Min Chou; Yong Cao; Huan Wang; Yong Zheng; Chenglong Li; Elham Hosseinzadehsabeti (Journal of Structural Geology, 2024)

Innovating for a greener world: Simulating low-carbon innovation in manufacturing companies from the lens of community succession - Yuguo Jiang; Hongxiang Yu; Enock Mintah Ampaw; Chenglong Wang; Ping Jiang (Journal of Cleaner Production, 2024)

Multiphase simulation of hyperbaric steam-water jet inside liquid Pb-Bi eutectic environment - Qifan Yu; Yafeng Zhao; Yutong Chen; Zhipeng Liu; Chenglong Wang; Dalin Zhang; Wenxi Tian; Suizheng Qiu; G.H. SU (Annals of Nuclear Energy, 2024)

Therapeutic effect of a self-made herbal formula on a multi-drug resistant Eimeria tenella isolate infection in broiler chickens - Chenglong Yu; Junjie Huang; Wei Tian; Yuying Huai; Shumei Zheng; Huiwen Wang; Jianhui Chen; Huimin Chen; Ruonan Bo; Jingui Li; Mingjiang Liu (Veterinary Parasitology, 2023)

Identifying and optimizing ecological spatial patterns based on the bird distribution in the Yellow River Basin, China - Chenglong Xu; Qiang Yu; Fei Wang; Shi Qiu; Mingsi Ai; Jikai Zhao (Journal of Environmental Management, 2023)

Laccase Lac-W detoxifies aflatoxin B1 and degrades five other major mycotoxins in the absence of redox mediators - Wen-Bo Hao; Xiaodan Gu; Xiaohu Yu; Youbao Zhao; Chenglong Li; Mengshuang Jia; Xiang-Dang Du (Environmental Pollution, 2023)

Study on impact of photovoltaic power tracking modes on photovoltaic-photothermal performance of PV-PCM-Trombe wall system - Xiaoxiao Su; Chenglong Luo; Xinzhu Chen; Toulong Nie; Yanshun Yu; Wu Zou; Yuandan Wu (Energy and Buildings, 2023)

A novel supported Mn-Ce catalyst with meso-microporous structure for low temperature synergistic removal of nitrogen oxides and toluene: structure–activity relationship and synergistic mechanism - Chenglong Yu; Xuehui Jia; Rong Liu; Hansun Fang; Jinliang Wang; Danping Li; Jiangbo Xiong; Junhui Dan; Zhenhua Dai; Lu Wang (Chemical Engineering Journal, 2023)

Removal characteristics of microplastics in sewage flowing through a long-term operation surface flow wetland - Le Zhang; Jingxin Wang; Xia Gong; Yaohua Song; Danping Li; Huajun Huang; Chenglong Yu; Ximei Liang; Hansun Fang (Science of The Total Environment, 2023)

Physicochemical and biological changes on naturally aged microplastic surfaces in real environments over 10 months - Xue Yu; Bing Wang; Chenglong Han; Ling Liu; Xiaoxin Han; Boyang Zheng; Bo Zhang; Jiawei Sun; Zhiyin Zhang; Weiqi Ma; Lifang Zhai; Xueqiang Lu (Environmental Pollution, 2023)

Potential grading refrigeration system? Based on urban agglomeration thermal environment analysis perspective - Shi Qiu; Chenglong Xu; Fei Wang; Qiang Yu (Sustainable Cities and Society, 2023)

Chromium isotopic compositions of a reef in the South China Sea: Biological effects and influence from early diagenetic Mn-oxides reduction - Xi Yu; Ziyao Fang; Xiaoqing He; Liang Yi; Chenglong Deng; Wen Yan; Liping Qin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Climatic effect from oyster reef restoration in Spartina alterniflora invaded intertidal mudflat: From the perspective of CH4 and N2O production - Wenjing Fu; Xiaoke Pang; Yifan Zhao; Chenglong Han; Yufei Liu; Xue Yu; Jianfeng Feng; Jing Fang; Bo Zhang; Xueqiang Lu (Estuarine, Coastal and Shelf Science, 2023)

Temporal framework for the Yanliao Biota and timing of the origin of crown mammals - Zhiqiang Yu; Haibing Wang; Chi Zhang; Liping Dong; Magdalena H. Huyskens; Zexian Cui; Paige Cary; Yankun Di; Yuri Amelin; Gang Li; Qiuli Li; Xiao-Ping Xia; et al. (Earth and Planetary Science Letters, 2023)

Sex-dependent associations of plasma high-density lipoprotein cholesterol and mortality risk in healthy older men and women: two prospective cohort studies - Sultana Monira Hussain; Andrew M Tonkin; Gerald F Watts; Paul Lacaze; Chenglong Yu; Lawrence J Beilin; Zhen Zhou; Anne B Newman; Johannes T Neumann; Cammie Tran; John J McNeil (GeroScience, 2023)
The relationship between high plasma high-density lipoprotein cholesterol (HDL-C) and cause and mortality are not well established in healthy older people. This study examined the associations between HDL-C levels and mortality in initially healthy older men and women. This analysis included participants from the Aspirin in Reducing Events in the Elderly (ASPREE; n =18,668) trial and a matched cohort from the UK Biobank (UKB; n =62,849 ≥65 years). Cox regression was used to examine hazard ratios between HDL-C categories <1.03 mmol/L, 1.03–1.55 mmol/L (referent category), 1.55–2.07 mmol/L, and >2.07 mmol/L and all-cause, cancer, cardiovascular disease (CVD), and “non-cancer non-CVD” mortality. Genetic contributions were assessed using a polygenic score for HDL-C. Among ASPREE participants (aged 75±5 years), 1836 deaths occurred over a mean follow-up of 6.3±1.8 years. In men, the highest category of HDL-C levels was associated with increased risk of all-cause (HR 1.60, 95% CI 1.26–2.03), cancer (HR 1.37, 95% CI 0.96–2.00), and “non-cancer non-CVD” mortality (HR 2.35, 95% CI 1.41–3.42) but not CVD mortality (HR 1.08, 95% CI 0.60–1.94). The associations were replicated among UKB participants (aged 66.9±1.5 years), including 8739 deaths over a mean follow-up of 12.7±0.8 years. There was a non-linear association between HDL-C levels and all-cause and cause-specific mortality. The association between HDL-C levels and mortality was unrelated to variations in the HDL-C polygenic score. No significant association was found between HDL-C levels and mortality in women. Higher HDL-C levels are associated with increased risk from cancer and “non-cancer non-CVD” mortality in healthy older men but no such relationship was observed in women.

Comprehensive magnetic analysis of the tephras in Middle-Late Pleistocene loess records of Serbia, and implications for tephra identification, correlation and loess chronology - Namier Namier; Qingzhen Hao; Xinbo Gao; Yu Fu; Slobodan B. Marković; Ulrich Hambach; Daniel Veres; Joseph A. Mason; Yang Song; Chenglong Deng; Milivoj B. Gavrilov; Rastko Marković; et al. (Quaternary Science Reviews, 2023)

An environment-friendly strategy to prepare oxygen-nitrogen-sulfur doped mesopore-dominant porous carbons for symmetric supercapacitors - Chenglong Liu; Renlu Yuan; Yanxin Yuan; Ruoyang Hou; Yang Liu; Wenya Ao; Junshen Qu; Mengyan Yu; Huaihe Song; Jianjun Dai (Fuel, 2023)

Heritable methylation marks associated with prostate cancer risk - James G. Dowty; Chenglong Yu; Mahnaz Hosseinpour; Jihoon Eric Joo; Ee Ming Wong; Tu Nguyen-Dumont; Joseph Rosenbluh; Graham G. Giles; Roger L. Milne; Robert J. MacInnis; Pierre-Antoine Dugué; Melissa C. Southey (Familial Cancer, 2023)
DNA methylation marks that are inherited from parents to offspring are known to play a role in cancer risk and could explain part of the familial risk for cancer. We therefore conducted a genome-wide search for heritable methylation marks associated with prostate cancer risk. Peripheral blood DNA methylation was measured for 133 of the 469 members of 25 multiple-case prostate cancer families, using the EPIC array. We used these families to systematically search the genome for methylation marks with Mendelian patterns of inheritance, then we tested the 1,000 most heritable marks for association with prostate cancer risk. After correcting for multiple testing, 41 heritable methylation marks were associated with prostate cancer risk. Separate analyses, based on 869 incident cases and 869 controls from a prospective cohort study, showed that 9 of these marks near the metastable epiallele VTRNA2-1 were also nominally associated with aggressive prostate cancer risk in the population.

ROS production upon groundwater oxygenation: Implications of oxidative capacity during groundwater abstraction and discharging - Yanting Zhang; Na Zhang; Chenglong Yu; Hui Liu; Songhu Yuan (Journal of Hydrology, 2023)

Organic ligands activate the dark formation of hydroxyl radicals (HO•) in surface soil/sediment: Yields, mechanisms, and applications - Yufan Yuan; Fangling Guan; Chenglong Yu; Danping Li; Faying Lai; Huajun Huang; Jinbao He; Yanpeng Gao; Hansun Fang (Journal of Hazardous Materials, 2023)

Comparison of water-caprock and CO2-water-caprock geochemical reactivity in the Triassic Heshanggou Formation of Ordos Basin - Xin Ma; Yujie Diao; Lei Fu; Jing Yan; Guodong Yang; Chenglong Zhang; Siyu Liu; Hanchuan Dong; Ying Yu (International Journal of Greenhouse Gas Control, 2023)

Study of spatialtemporal changes in Chinese forest eco-space and optimization strategies for enhancing carbon sequestration capacity through ecological spatial network theory - Shi Qiu; Minzhe Fang; Qiang Yu; Teng Niu; Hongjun Liu; Fei Wang; Chenglong Xu; Mingsi Ai; Jieyu Zhang (Science of The Total Environment, 2023)

Climatic factors and human population changes in Eurasia between the Last Glacial Maximum and the early Holocene - Yanyan Yu; Feng He; Stephen J. Vavrus; Amber Johnson; Haibin Wu; Wenchao Zhang; Qiuzhen Yin; Junyi Ge; Chenglong Deng; Michael D. Petraglia; Zhengtang Guo (Global and Planetary Change, 2023)

Corrigendum to “Comparison of carrying mechanism between three fat-soluble vitamins and alpha-lactalbumin: Effects on structure and physicochemical properties of alpha-lactalbumin” [Food Hydrocolloids 116 (2021) 106662] - Wei Chen; Haiying Yu; Ruijie Shi; Chenglong Ma; Munkh-Amgalan Gantumur; Abdul Qayum; Akhunzada Bilawal; Guizhao Liang; Kwang-Chol Oh; Zhanmei Jiang; Juncai Hou (Food Hydrocolloids, 2023)

An integrated framework for wide-area active landslide detection with InSAR observations and SAR pixel offsets - Chenglong Zhang; Zhenhong Li; Chen Yu; Bo Chen; Mingtao Ding; Wu Zhu; Jing Yang; Zhenjiang Liu; Jianbing Peng (Landslides, 2022)

Exploring the R-ISS stage-specific regular networks in the progression of multiple myeloma at single-cell resolution - Ling Zhong; Xiao Yang; Yu Zhou; Jialing Xiao; Huan Li; Jiang Tao; Qian Xi; Chen Chu; Chenglong Li; Xi Yang; Chen Yang; Yi Zhang; et al. (Science China Life Sciences, 2022)

sVCAM1 in the Hippocampus Contributes to Postoperative Cognitive Dysfunction in Mice by Inducing Microglial Activation Through the VLA-4 Receptor - Chenglong Li; Qi Li; Shuai Liu; Jiaying Li; Wei Yu; Yan Li; Ruirui Zhang; Sihua Qi (Molecular Neurobiology, 2022)

Size distribution, emission rate, and decay characteristics of particles emitted by printers - Changwei Zou; Miaoting Jiang; Hong Huang; Hunan Chen; Li Sheng; Jianlong Li; Chenglong Yu (Air Quality, Atmosphere & Health, 2022)

Trachyte reservoir characteristics and favorable reservoir identification and prediction in the J34 block, Eastern Sag - Chenglong Ma; Ying Wu; Tuan Gu; Bin Zhang; Yu Gang Li; Ying Jie Zhang; Wen Bo Dong; Jie Cui (Acta Geophysica, 2022)

A Brief Overview of Global Trends in MSC-Based Cell Therapy - Dragomirka Jovic; Yingjia Yu; Dan Wang; Kuixing Wang; Hanbo Li; Fengping Xu; Chenglong Liu; Junnian Liu; Yonglun Luo (Stem Cell Reviews and Reports, 2022)

Characteristics of the BDS-3 multipath effect and mitigation methods using precise point positioning - Ran Lu; Wen Chen; Chenglong Zhang; Lei Li; Yu Peng; Zhengqi Zheng (GPS Solutions, 2022)

Mesenchymal Stem Cell Derived Exosomes Suppress Neuronal Cell Ferroptosis Via lncGm36569/miR-5627-5p/FSP1 Axis in Acute Spinal Cord Injury - Chenglong Shao; Yu Chen; Tengyue Yang; Haibiao Zhao; Dongzhe Li (Stem Cell Reviews and Reports, 2022)

Evaluation of the carbon sequestration of Zhalong Wetland under climate change - Chenglong Yu; Dan Liu; Huiying Zhao (Journal of Geographical Sciences, 2021)

Multipath mitigation in GNSS precise point positioning based on trend-surface analysis and multipath hemispherical map - Ran Lu; Wen Chen; Danan Dong; Zhiren Wang; Chenglong Zhang; Yu Peng; Chao Yu (GPS Solutions, 2021)

SIMS U-Pb geochronology for the Jurassic Yanliao Biota from Bawanggou section, Qinglong (northern Hebei Province, China) - Zhiqiang Yu; Huaiyu He; Gang Li; Chenglong Deng; Haibing Wang; Xinxin Zhang; Qing Yang; Xiao-Ping Xia; Zhonghe Zhou; Rixiang Zhu (International Geology Review, 2021)

Geochronology and Geochemistry of the 890 Ma I-Type Granites in the Southwestern Yangtze Block: Petrogenesis and Crustal Evolution - Jibiao Zhang; Xiaozhong Ding; Yanxue Liu; Heng Zhang; Chenglong Shi; Yu Zou (Journal of Earth Science, 2020)

Response of the water use efficiency of natural vegetation to drought in Northeast China - Dan Liu; Chenglong Yu; Fang Zhao (Journal of Geographical Sciences, 2018)

Evaluating Nonlinear Sorption of Four Substituted Phenols to Agriculture Soils Using Expanded Polyparameter Linear Free Energy Relationship - Chenglong Yu; Erping Bi (Water, Air, & Soil Pollution, 2017)

Basidiomycete‐specific PsCaMKL1 encoding a CaMK‐like protein kinase is required for full virulence of Puccinia striiformis f. sp. tritici - Min Jiao; Dan Yu; Chenglong Tan; Jia Guo; Dingyun Lan; Ershang Han; Tuo Qi; Ralf Thomas Voegele; Zhensheng Kang; Jun Guo (Environmental Microbiology, 2017)
Summary Calcium/calmodulin‐dependent kinases (CaMKs) are Ser/Thr protein kinases (PKs) that respond to changes in cytosolic free Ca 2+ and play diverse roles in eukaryotes. In fungi, CAMKs are generally classified into four families CAMK1, CAMKL, RAD53 and CAMK‐Unique. Among these, CAMKL constitutes the largest family. In some fungal plant pathogens, members of the CaMKL family have been shown to be responsible for pathogenesis. However, little is known about their role(s) in rust fungi. In this study, we functionally characterized a novel PK gene, PsCaMKL1 , from Puccinia striiformis f. sp. tritici ( Pst ). Ps CaMKL1 belongs to a group of PKs that is evolutionarily specific to basidiomyceteous fungi. Ps CaMKL1 shows little intra‐species polymorphism between Pst isolates. PsCaMKL1 transcripts are highly elevated at early infection stages, whereas gene expression is downregulated in barely germinated urediospores under KN93 treatment. Overexpression of PsCaMKL1 in fission yeast increased resistance to environmental stresses. Knock down of PsCaMKL1 using host‐induced gene silencing (HIGS) reduced the virulence of Pst accompanied by reactive oxygen species (ROS) accumulation and a hypersensitive response. These results suggest that Ps CaMKL1 is a novel pathogenicity factor that exerts it virulence function by regulating ROS production in wheat.

Manganese-rich MnSAPO-34 molecular sieves as an efficient catalyst for the selective catalytic reduction of NO x with NH3: one-pot synthesis, catalytic performance, and characterization - Chenglong Yu; Feng Chen; Lifu Dong; Xiaoqing Liu; Bichun Huang; Xinnan Wang; Shengbang Zhong (Environmental Science and Pollution Research, 2017)

Differential metabolic responses in three life stages of mussels Mytilus galloprovincialis exposed to cadmium - Huifeng Wu; Lanlan Xu; Deliang Yu; Chenglong Ji (Ecotoxicology, 2017)

Distribution, sources, and ecological risk assessment of polycyclic aromatic hydrocarbons in the water and suspended sediments from the middle and lower reaches of the Yangtze River, China - Chenglong Wang; Xinqing Zou; Yifei Zhao; Baojie Li; Qiaochu Song; Yali Li; Wenwen Yu (Environmental Science and Pollution Research, 2016)

Dynamic response of a riser under excitation of internal waves - Min Lou; Chenglong Yu; Peng Chen (Journal of Ocean University of China, 2015)

Ectopic Expression of Fagopyrum tataricum FtMYB12 Improves Cold Tolerance in Arabidopsis thaliana - Meiliang Zhou; Chenglong Wang; Leipeng Qi; Xiongbang Yang; Zhanmin Sun; Yu Tang; Yixiong Tang; Jirong Shao; Yanmin Wu (Journal of Plant Growth Regulation, 2015)

HMGB1 Silencing Potentiates the Anti-inflammatory Effects of Sodium Ferulate in ox-LDL-Stimulated Vascular Smooth Muscle Cells - Nan Hu; Lingshang Kong; Aimin Qian; Qingyou Meng; Chenglong Li; Xiaobin Yu; Hong Chen; Xiaolong Du; Xiaoqiang Li (Cell Biochemistry and Biophysics, 2015)

XZH-5 inhibits STAT3 phosphorylation and causes apoptosis in human hepatocellular carcinoma cells - Yan Liu; Aiguo Liu; Zhenghu Xu; Wenying Yu; Hong Wang; Chenglong Li; Jiayuh Lin (Apoptosis, 2011)

Generation and characterization of transgenic poplar plants overexpressing a cotton laccase gene - Ji Wang; Chenglong Wang; Mulan Zhu; Yang Yu; Yuebo Zhang; Zhiming Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)